Supply chain governance in the context of industry 4.0: Investigating implications of real-life implementations from a multi-tier perspective - Pfaff, Yuko; Birkel, Hendrik; Hartmann, Evi (International Journal of Production Economics, 2023)
This paper addresses the impact of Industry 4.0 (I4.0) on supply chain governance (SCG) mechanisms within inter-organizational relationships in a multi-tier context. Special emphasis is paid to the investigation of the dynamics and outcome with regard to the structure and management of the relationships along the multi-tier. A multiple case study method is applied to explain the impact of I4.0 based on a theory-grounded research framework through the lens of complementary SCM theories. Building on qualitative in-depth interviews with 19 experts in managerial positions, three cases from the manufacturing industry involving an I4.0 implementation across the multi-tier were analyzed. This research demonstrates an intensification of synergistic combinations of inter-firm resources, emphasizing SCG as essential. With the implementation of I4.0, competitive advantage along the multi-tier takes higher priority over the competitive advantage in the individual or dyadic perspective. Relational governance mechanisms evolve, allowing competitive advantage as a multi-tier balancing out traditional power mechanisms within the supply chain hierarchy. Findings show that contractual governance mechanisms are limited in their effect, revealing the need for an evolution of “relational contracting.” Finally, the case research proposes “agility” as an extended mechanism in SCG research. The study offers in-depth insights into the structure of SCG mechanisms and the implications of adapted SCG on SCM outcomes to redesign multi-tier relationships. Supported by SCM theories and the dimensions of SCG, this paper contributes to the first insights beyond the dyadic perspective, providing an integrated multi-tier perspective while discussing specific mechanisms and identifying relevant propositions for future researc